Estudio de prefactibilidad para la instalación de una empresa que brinde el servicio de compra para el menú del hogar con un enfoque de servicio integral - Crespo Bulnes, Patricia (2016)
The purpose of this project is to analyze the business process of logistics service regarding the purchase of the supplied food for Peruvian market, through a pre-feasibility study. In Peru, this type of business is limited to just a few suppliers, although in the world, this business have several years of development and is constantly growing as a result of changes in consumer habits and consumer concerns: “greater comfort and longer time for their personal activities without influencing in quality and food safety.